A Response to "Participation: A Religious Worldview" by James M. Gustafson. Issue 1 (March 2016) - Schweiker, William
Abstract: This response offers an interpretation of James Gustafson's "Participation: A Religious Worldview, " which thinks with Gustafson on the theme of "participation, " while highlighting points where my own thoughts diverge from his. The essay begins by drawing the reader's attention to Gustafson's style, arguing that the simple elegance of his writing constitutes part of his larger claim about the need to remove ourselves from the center of our thought. Next, the essay analyzes Gustafson's use of "participation" by putting it in context and connecting it with his broader methodology. Finally, I draw the reader's attention to important loci in the text in order to show how Gustafson's essay helps address various extant misinterpretations of his thought but also to point to ways in which my "thinking with" Gustafson leads me to think otherwise than he does.